2005
DOI: 10.1128/jb.187.12.3980-3989.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bacteriocin Production in Streptococcus mutans by the Quorum-Sensing System Required for Development of Genetic Competence

Abstract: In Streptococcus mutans, competence for genetic transformation and biofilm formation are dependent on the two-component signal transduction system ComDE together with the inducer peptide pheromone competencestimulating peptide (CSP) (encoded by comC). Here, it is shown that the same system is also required for expression of the nlmAB genes, which encode a two-peptide nonlantibiotic bacteriocin. Expression from a transcriptional nlmAB-lacZ fusion was highest at high cell density and was increased up to 60-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
248
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(264 citation statements)
references
References 34 publications
13
248
1
2
Order By: Relevance
“…The results showed that, similar to the microarray data, comYA and comX were indeed downregulated at pH 5.5, but comE and the two bacteriocin-related genes were upregulated at this pH (Table 2). These results are surprising, since the ComCDE quorum sensing system in S. mutans is known to control both genetic competence and bacteriocin production (Li et al, 2001a;van der Ploeg, 2005). One may expect the same impact when the ComCDE signal pathway is activated.…”
Section: Downregulated Genesmentioning
confidence: 54%
“…The results showed that, similar to the microarray data, comYA and comX were indeed downregulated at pH 5.5, but comE and the two bacteriocin-related genes were upregulated at this pH (Table 2). These results are surprising, since the ComCDE quorum sensing system in S. mutans is known to control both genetic competence and bacteriocin production (Li et al, 2001a;van der Ploeg, 2005). One may expect the same impact when the ComCDE signal pathway is activated.…”
Section: Downregulated Genesmentioning
confidence: 54%
“…comD encodes the histidine kinase receptor to response to competence-stimulating peptide (CSP), and comE encodes an intracellular response regulator to mediate expressions of downstream genes. Activated ComE enables the production of mutacin Ⅳ and â…€, as well as genetic competence [49]. Significant downregulation of comDE was also observed in the 1/2 MIC group, and downregulation of comDE by 1/2 MIC of GH12 suppresses regulation of genetic competence and intra-species cell–cell communication.…”
Section: Discussionmentioning
confidence: 99%
“…If the host immune surveillance system has not yet activated IDO (with its consequence of Trp depletion), then sufficient Trp nutrients will exist to support the full expression of the competent state. Cells in the competent state may confer certain temporary growth advantages, such as the ability to utilize DNA as a source of nutrients such as carbon, nitrogen, and phosphorus (e.g., as speculated by van der Ploeg [130]). Yet competence is at the same time a fragile physiological state.…”
Section: Extracellular Pathogensmentioning
confidence: 99%